Classical biological of key horticultural pests in Africa: successes, challenges, and opportunities - Mohamed, S.; Dubois, T.; Azrag, A.G.A.; Ndlela, S.; Neuenschwander, Peter (Elsevier, 2022)
Classical biological control (CBC) is considered a safer and more sustainable alternative for management of alien-invasive species. This review presents recent advances in CBC of key horticultural insect pests using parasitoids in Africa. Several CBC programs have been undertaken targeting different insect pests of both fruits and vegetables, largely yielding outstanding success. Key obstacles impeding CBC and opportunities that could promote CBC in Africa are outlined. Also, very brief highlights on recent scientific and technological advances in modeling, integrative taxonomy and molecular tools, and endosymbionts that relate to CBC are provided.